Role of women in development on gender perspective in Indonesia - Maria K Tupamahu; Criezta Kolefura (The International Journal of Politics and Sociology Research, 2023)
This paper aimed to reveal the role (rights and obligations) of women in gendered development. Gender-oriented development is intended to realize a harmonious gender-oriented development is intended to realise a harmonious partnership between men and women or to realise gender equality and justice in a variety of and women or realising gender equality and justice in various fields of life and development. Gender mainstreaming is the right strategy to accelerate the realisation of gender equality and justice..This research model tries with all its might to elaborate various scientific sources that will strongly support the construction of the analysis of a particular study. This research method is a qualitative research method with a descriptive approach. This research operationally examines various sources of literature relevant to the context of the above research. According to the general theoretical view of experts, the social reality of conditions that disadvantage women in terms of gender conditions that disadvantage women in gender issues, is the result of a long process of historical and socio-cultural.